Comparison of the Effect of Yakson Touch and Oral Glucose on the Severity of Phlebotomy Pain in Preterm Infants - Khadijeh Dehghani; Akram Bagheri Ahmadabadi; Hossein Fallahzade; Tahere Salimi (Mashhad University of Medical Sciences, 2019)
Background: Infants are exposed to different painful procedures during hospitalization in the neonatal intensive care unit (NICU). Due to the harmful effects of pain on infants, NICUs require methods by the aid of which the pain in infants can be controlled. Yakson touch and oral glucose are among non-pharmacological methods for pain relief in infants. In this regard, the present study was conducted to compare the effect of Yakson touch and oral glucose on the severity of phlebotomy pain in preterm infants. Methods: In this randomized clinical trial, 99 preterm infants hospitalized in NICU were randomly allocated to three groups, including Yakson touch (n=33), oral glucose (n=33), and control (n=33). In the oral glucose group, 1 cc of 50% glucose was orally given to the infants 1 min before phlebotomy. In the Yakson touch group, touching was performed for 5 min, and then the phlebotomy was performed. The infants in the control group did not receive a specific treatment. Infant pain level was determined before and after the phlebotomy using video recording based on Neonatal Infant Pain Scale. The data were analyzed using the analytical statistical tests, including the analysis of variance, Chi-square, Wilcoxon, and Kruskal-Wallis, in SPSS software (version 20). Results: The mean scores of pain in the two experimental groups were significantly lower than that of the control group (P=0.001), but there was no significant difference between the two experimental groups (P>0.05). Conclusion: According to our findings, both two methods (i.e., Yakson touch and oral glucose) can reduce phlebotomy pain in preterm infants hospitalized in intensive care unit. It is recommended to use Yakson touch in case of lack of access to glucose.